Global Economic Prospects and the Developing Countries 1994 - World Bank (Washington, DC: World Bank, 2019)
This year’s report gives special attention to international trade in commodities, a subject of central importance to many developing countries, as commodity exports continue to be a large component of their total exports. Chapter 1 deals with global conditions and prospects for developing countries. Chapters 2 and 3 examine trends in international commodity markets and implications of commodity dependence for growth and development in low-income countries.